Studies on the Natural Resistance of Timbers to Termite Attack, V. Laboratory Evaluation of the Resistance of Three Species of Indian Wood to Microcerotermes beesoni Snyder (Termitidae : Amitermitinae) - Sen-Sarma, P. K.; Chatterjee, P. N. (Indian Forester, 1968)
Natural resistance of three species of Indian woods, namely, ’axle-wood’, ’mahua’ and ’teak’, to Microcerotermes beesoni, a subterranean termite species, has been discussed. Techniques of sampling of wood, culturing of termites and testing of resistance of wood to termites have been given in detail. The heartwood of’mahua’ and ’teak’ may be classed as very resistant to termites while wood of ’axle-wood’ is only moderately resistant to termites.